In-situ decomposition sensor output correlates with soil health indicators - Taylor J. Sharpe; Madhur Atreya; Shangshi Liu; Mengyi Gong; Nicole Luna; Noah Smock; Jessica Davies; John N. Quinton; Richard D. Bardgett; Jason C. Neff; Rebecca Killick; Gregory L. Whiting (Computers and Electronics in Agriculture, 2026)

Healthy soils as a booster to EU competitiveness - Panos Panagos; Alberto Orgiazzi; Emanuele Lugato; Guillaume Vandenesch; Laurent Thannberger; Jason C. Neff; Arjan Reijneveld; Erik Mathijs; Pascal Chapot; Sara Guerrini; Darina Štyriaková; Julian Kremers; et al. (Land Use Policy, 2025)

Predicting spatiotemporal soil organic carbon responses to management using EPIC-IIASA meta-models - Tara Ippolito; Juraj Balkovič; Rastislav Skalsky; Christian Folberth; Tamas Krisztin; Jason Neff (Journal of Environmental Management, 2023)

Bee phenology is predicted by climatic variation and functional traits - Michael Stemkovski; William D. Pearse; Sean R. Griffin; Gabriella L. Pardee; Jason Gibbs; Terry Griswold; John L. Neff; Ryan Oram; Molly G. Rightmyer; Cory S. Sheffield; Karen Wright; Brian D. Inouye; et al. (Ecology Letters, 2020)
Climate change is shifting the environmental cues that determine the phenology of interacting species. Plant–pollinator systems may be susceptible to temporal mismatch if bees and flowering plants differ in their phenological responses to warming temperatures. While the cues that trigger flowering are well‐understood, little is known about what determines bee phenology. Using generalised additive models, we analyzed time‐series data representing 67 bee species collected over 9 years in the Colorado Rocky Mountains to perform the first community‐wide quantification of the drivers of bee phenology. Bee emergence was sensitive to climatic variation, advancing with earlier snowmelt timing, whereas later phenophases were best explained by functional traits including overwintering stage and nest location. Comparison of these findings to a long‐term flower study showed that bee phenology is less sensitive than flower phenology to climatic variation, indicating potential for reduced synchrony of flowers and pollinators under climate change.

Species, Climate and Landscape Physiography Drive Variable Growth Trends in Subalpine Forests - Katharine C. Kelsey; Miranda D. Redmond; Nichole N. Barger; Jason C. Neff (Ecosystems, 2018)

Aerosol Deposition Impacts on Land and Ocean Carbon Cycles - Natalie M. Mahowald; Rachel Scanza; Janice Brahney; Christine L. Goodale; Peter G. Hess; J. Keith Moore; Jason Neff (Current Climate Change Reports, 2017)

Managing Carbon on Federal Public Lands: Opportunities and Challenges in Southwestern Colorado - Lisa Dilling; Katharine C. Kelsey; Daniel P. Fernandez; Yin D. Huang; Jana B. Milford; Jason C. Neff (Environmental Management, 2016)

Mid-21st century projections in temperature extremes in the southern Colorado Rocky Mountains from regional climate models - Imtiaz Rangwala; Joseph Barsugli; Karen Cozzetto; Jason Neff; James Prairie (Climate Dynamics, 2012)

Vegetation Effects on Soil Organic Matter Chemistry of Aggregate Fractions in a Hawaiian Forest - Catherine E. Stewart; Jason C. Neff; Kathryn L. Amatangelo; Peter M. Vitousek (Ecosystems, 2011)

Interactive Effects of Fire, Soil Climate, and Moss on CO2 Fluxes in Black Spruce Ecosystems of Interior Alaska - Jonathan A. O’Donnell; Merritt R. Turetsky; Jennifer W. Harden; Kristen L. Manies; Lee E. Pruett; Gordon Shetler; Jason C. Neff (Ecosystems, 2009)

The effects of chronic nitrogen fertilization on alpine tundra soil microbial communities: implications for carbon and nitrogen cycling - Diana R. Nemergut; Alan R. Townsend; Sarah R. Sattin; Kristen R. Freeman; Noah Fierer; Jason C. Neff; William D. Bowman; Christopher W. Schadt; Michael N. Weintraub; Steven K. Schmidt (Environmental Microbiology, 2008)
Summary Many studies have shown that changes in nitrogen (N) availability affect primary productivity in a variety of terrestrial systems, but less is known about the effects of the changing N cycle on soil organic matter (SOM) decomposition. We used a variety of techniques to examine the effects of chronic N amendments on SOM chemistry and microbial community structure and function in an alpine tundra soil. We collected surface soil (0–5 cm) samples from five control and five long‐term N‐amended plots established and maintained at the Niwot Ridge Long‐term Ecological Research (LTER) site. Samples were bulked by treatment and all analyses were conducted on composite samples. The fungal community shifted in response to N amendments, with a decrease in the relative abundance of basidiomycetes. Bacterial community composition also shifted in the fertilized soil, with increases in the relative abundance of sequences related to the Bacteroidetes and Gemmatimonadetes , and decreases in the relative abundance of the Verrucomicrobia . We did not uncover any bacterial sequences that were closely related to known nitrifiers in either soil, but sequences related to archaeal nitrifiers were found in control soils. The ratio of fungi to bacteria did not change in the N‐amended soils, but the ratio of archaea to bacteria dropped from 20% to less than 1% in the N‐amended plots. Comparisons of aliphatic and aromatic carbon compounds, two broad categories of soil carbon compounds, revealed no between treatment differences. However, G‐lignins were found in higher relative abundance in the fertilized soils, while proteins were detected in lower relative abundance. Finally, the activities of two soil enzymes involved in N cycling changed in response to chronic N amendments. These results suggest that chronic N fertilization induces significant shifts in soil carbon dynamics that correspond to shifts in microbial community structure and function.

Dissolved Organic Carbon in Alaskan Boreal Forest: Sources, Chemical Characteristics, and Biodegradability - Kimberly P. Wickland; Jason C. Neff; George R. Aiken (Ecosystems, 2007)

Effects of wildfire and permafrost on soil organic matter and soil climate in interior Alaska - JENNIFER W. HARDEN; KRISTEN L. MANIES; MERRITT R. TURETSKY; JASON C. NEFF (Global Change Biology, 2006)
The influence of discontinuous permafrost on ground‐fuel storage, combustion losses, and postfire soil climates was examined after a wildfire near Delta Junction, AK in July 1999. At this site, we sampled soils from a four‐way site comparison of burning (burned and unburned) and permafrost (permafrost and nonpermafrost). Soil organic layers (which comprise ground‐fuel storage) were thicker in permafrost than nonpermafrost soils both in burned and unburned sites. While we expected fire severity to be greater in the drier site (without permafrost), combustion losses were not significantly different between the two burned sites. Overall, permafrost and burning had significant effects on physical soil variables. Most notably, unburned permafrost sites with the thickest organic mats consistently had the coldest temperatures and wettest mineral soil, while soils in the burned nonpermafrost sites were warmer and drier than the other soils. For every centimeter of organic mat thickness, temperature at 5 cm depth was about 0.5°C cooler during summer months. We propose that organic soil layers determine to a large extent the physical and thermal setting for variations in vegetation, decomposition, and carbon balance across these landscapes. In particular, the deep organic layers maintain the legacies of thermal and nutrient cycling governed by fire and revegetation. We further propose that the thermal influence of deep organic soil layers may be an underlying mechanism responsible for large regional patterns of burning and regrowth, detected in fractal analyses of burn frequency and area. Thus, fractal geometry can potentially be used to analyze changes in state of these fire prone systems.

Composition, Dynamics, and Fate of Leached Dissolved Organic Matter in Terrestrial Ecosystems: Results from a Decomposition Experiment - Cory C. Cleveland; Jason C. Neff; Alan R. Townsend; Eran Hood (Ecosystems, 2004)

Vegetation and climate controls on potential CO 2 , DOC and DON production in northern latitude soils - Jason C. Neff; David U. Hooper (Global Change Biology, 2002)
Climatic change may influence decomposition dynamics in arctic and boreal ecosystems, affecting both atmospheric CO 2 levels, and the flux of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) to aquatic systems. In this study, we investigated landscape‐scale controls on potential production of these compounds using a one‐year laboratory incubation at two temperatures (10° and 30 °C). We measured the release of CO 2 , DOC and DON from tundra soils collected from a variety of vegetation types and climatic regimes: tussock tundra at four sites along a latitudinal gradient from the interior to the north slope of Alaska, and soils from additional vegetation types at two of those sites (upland spruce at Fairbanks, and wet sedge and shrub tundra at Toolik Lake in northern Alaska). Vegetation type strongly influenced carbon fluxes. The highest CO 2 and DOC release at the high incubation temperature occurred in the soils of shrub tundra communities. Tussock tundra soils exhibited the next highest DOC fluxes followed by spruce and wet sedge tundra soils, respectively. Of the fluxes, CO 2 showed the greatest sensitivity to incubation temperatures and vegetation type, followed by DOC. DON fluxes were less variable. Total CO 2 and total DOC release were positively correlated, with DOC fluxes approximately 10% of total CO 2 fluxes. The ratio of CO 2 production to DOC release varied significantly across vegetation types with Tussock soils producing an average of four times as much CO 2 per unit DOC released compared to Spruce soils from the Fairbanks site. Sites in this study released 80–370 mg CO 2 ‐C g soil C −1 and 5–46 mg DOC g soil C −1 at high temperatures. The magnitude of these fluxes indicates that arctic carbon pools contain a large proportion of labile carbon that could be easily decomposed given optimal conditions. The size of this labile pool ranged between 9 and 41% of soil carbon on a g soil C basis, with most variation related to vegetation type rather than climate.

Dissolved Organic Carbon in Terrestrial Ecosystems: Synthesis and a Model - Jason C. Neff; Gregory P. Asner (Ecosystems, 2001)

Effects of Soil Texture on Belowground Carbon and Nutrient Storage in a Lowland Amazonian Forest Ecosystem - Whendee L. Silver; Jason Neff; Megan McGroddy; Ed Veldkamp; Michael Keller; Raimundo Cosme (Ecosystems, 2000)